2021
DOI: 10.1021/acs.analchem.1c00053
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Reactivity Mapping of a Single-Crystal Boron-Doped Diamond Particle

Abstract: Boron-doped diamond (BDD) is most often grown by chemical vapor deposition (CVD) in polycrystalline form, where the electrochemical response is averaged over the whole surface. Deconvoluting the impact of crystal orientation, surface termination, and boron-doped concentration on the electrochemical response is extremely challenging. To tackle this problem, we use CVD to grow isolated single-crystal microparticles of BDD with the crystal facets (100, square-shaped) and (111, triangle-shaped) exposed and combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 49 publications
1
22
0
Order By: Relevance
“…Scanning electrochemical cell microscopy (SECCM), which uses a micro/nanopipette as a probe, is an effective tool for visualizing sample surface reactivity as a faradic current 2D image. SECCM was used to characterize the charge/discharge of the composite cathode electrode, the metal oxide coated thin-film cathode electrode, and the thin-film anode electrode . SECCM is an effective tool that visualizes the nanoscale charge/discharge property and characterizes the heterogeneity of the individual active material’s charge/discharge property for LIBs.…”
mentioning
confidence: 99%
“…Scanning electrochemical cell microscopy (SECCM), which uses a micro/nanopipette as a probe, is an effective tool for visualizing sample surface reactivity as a faradic current 2D image. SECCM was used to characterize the charge/discharge of the composite cathode electrode, the metal oxide coated thin-film cathode electrode, and the thin-film anode electrode . SECCM is an effective tool that visualizes the nanoscale charge/discharge property and characterizes the heterogeneity of the individual active material’s charge/discharge property for LIBs.…”
mentioning
confidence: 99%
“…The electrochemical activity of isolated single‐crystal boron‐doped diamond (BDD) microparticles (width ≈ 3–10 μm, height ≈ 5–7 μm) toward two outer‐sphere redox processes, [Ru(NH 3 ) 6 ] 3+/2+ and [Fe(CN) 6 ] 4−/3− , was recently reported. [ 51 ] Through spatially‐resolved i − E measurements, it was unequivocally shown that for H‐terminated BDD, the triangle‐shaped false{111false}$\{ {111} \}$ facets support more rapid ET kinetics than the square‐shaped false{100false}$\{ {100} \}$ facets, attributed to the higher boron dopant density (i.e., more metal‐like character) of the former. Changing from H‐termination to O‐termination significantly impacted the electrochemical response of the BDD.…”
Section: Electrochemical Imagingmentioning
confidence: 99%
“…SECCM is particularly attractive for nanoparticle and nanosheet studies, whereby the electrocatalytic activity of individual nanoparticles or nanosheets within an ensemble can be measured and correlated with the structure or morphology obtained from colocated complementary surface analysis. 121 Choi et al 122 measured HER of single Au nanoparticles expressing predominantly {100} or {111} crystal planes on the surface by using SECCM (Figure 6A). They found that Au 100 nanoparticles have superior HER electrocatalytic activity compared to that of Au 111 nanoparticles.…”
Section: Nanopipette Applicationsmentioning
confidence: 99%